2011
DOI: 10.1111/j.1948-7134.2011.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Sub-additive effect of conspecific eggs and frass on oviposition rate of Lutzomyia longipalpis and Phlebotomus papatasi

Abstract: Oviposition behavior is a fairly neglected aspect in our understanding of the biology of sand flies. In this study, we used a comparative approach using both new-and old-world species (Lutzomyia longipalpis and Phlebotomus papatasi) in choice and no-choice oviposition chambers to evaluate the effect of old sand fly colony remains (frass), conspecific eggs, and their combination on oviposition rates of these sand flies. We also tested the effect of egg washing with de-ionized water on oviposition rates. In both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
(41 reference statements)
3
10
1
Order By: Relevance
“…Thus, sand flies laid most of their egg clutch once they became physiologically capable of doing so (72–96 h post blood-meal) and then laid additional 1.8 eggs (per capita) approximately every 24 h. Schlein et al [ 41 ] did not observe a sudden increase in oviposition at a particular day but they did observe continuously increasing cumulative egg number between days 7 and 14 post blood-meal. Per-capita egg deposition observed in our study (13.25 per female) is lower than the 15–20 eggs-per-female previously reported by Wasserberg and Rowton [ 28 ] or the 33.44 eggs-per-female observed by T. Rowland (personal observations) for individually-reared Ph. papatasi .…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…Thus, sand flies laid most of their egg clutch once they became physiologically capable of doing so (72–96 h post blood-meal) and then laid additional 1.8 eggs (per capita) approximately every 24 h. Schlein et al [ 41 ] did not observe a sudden increase in oviposition at a particular day but they did observe continuously increasing cumulative egg number between days 7 and 14 post blood-meal. Per-capita egg deposition observed in our study (13.25 per female) is lower than the 15–20 eggs-per-female previously reported by Wasserberg and Rowton [ 28 ] or the 33.44 eggs-per-female observed by T. Rowland (personal observations) for individually-reared Ph. papatasi .…”
Section: Discussioncontrasting
confidence: 81%
“…Phlebotomus papatasi , the main vector of Old-World cutaneous leishmaniasis (due to Leishmania major ), is distributed from Morocco to the Indian subcontinent and from southern Europe to central and eastern Africa [ 3 , 4 , 27 ]. It was shown to lay more eggs on substrates containing conspecific eggs [ 28 , 29 ] or organic matter of various sources [ 29 , 30 ]. For example, Wasserberg and Rowton [ 28 ] compared the relative effectiveness of conspecific eggs and organic matter (frass extract) and found frass to be a much more potent oviposition stimulant than eggs; they also found that the combination of eggs and frass was not more effective than frass alone.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…longipalpis preferred sites for oviposition that contain frass or rabbit faeces, which act as its larval rearing medium. More recently, Wasserberg and Rowton (2011) demonstrated that in choice and no-choice oviposition chambers, the effect of old sandfly colony remains (frass), conspecific eggs and their combination affected the oviposition rates of sandflies (Peterkova-Koci et al 2012). The present study will contribute to the development of a methodology for the maintenance of sandfly colonies, which is a major challenge for scientists working on different biological aspects of sandflies.…”
mentioning
confidence: 99%